2007
DOI: 10.1111/j.1742-7843.2007.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Chromium‐Molybdenum Alloy Causes Metal Accumulation and Metallothionein Up‐Regulation in Rat Liver and Kidney

Abstract: Cobalt-chromium-molybdenum (CoCrMo) metal-on-metal hip prosthesis has had a revival due to their excellent wear properties. However, particulate wear debris and metal ions liberated from the CoCrMo alloys might cause carcinogenicity, hypersensitivity, local and general tissue toxicity, genotoxicity and inflammation-generating qualities. Nine months after implanting small pieces of CoCrMo alloy intramuscularly and intraperitoneally in rats, we analysed the accumulation of metals with a multi-element analysis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 54 publications
1
25
0
1
Order By: Relevance
“…Thus, they can only be eliminated from tissues by renal or gastrointestinal excretion (Cobb and Schmalzreid 2006). There is evidence from a recent animal study to suggest that Cr ions can accumulate in the liver (Jakobsen et al 2007). Marker et al (2007) investigated potential long-term effects on kidney function resulting from Co and Cr wear in MoM THA by measuring serum metal ion levels and creatinine clearance at 10-year follow-up in 75 patients.…”
Section: Mom Hip Resurfacing Arthroplastymentioning
confidence: 99%
“…Thus, they can only be eliminated from tissues by renal or gastrointestinal excretion (Cobb and Schmalzreid 2006). There is evidence from a recent animal study to suggest that Cr ions can accumulate in the liver (Jakobsen et al 2007). Marker et al (2007) investigated potential long-term effects on kidney function resulting from Co and Cr wear in MoM THA by measuring serum metal ion levels and creatinine clearance at 10-year follow-up in 75 patients.…”
Section: Mom Hip Resurfacing Arthroplastymentioning
confidence: 99%
“…The existence of metals in both ionic and particulate form does initiate both innate and adaptive immune responses. Inflammatory, cytotoxic, and immunological responses appear to be interactive, because the exposure of metal debris to the acidic environment of the phagosome [49] or dissolucytosis at the macrophage surface [40] can elevate the generation of metal ions, intracellular metal ions can influence activities relevant to the immunological responses, and local hypersensitivity reactions can increase inflammation and tissue damage (Table 3). Genetic regulation of the responses will affect the overall pathology and outcome to metal debris, and thus it becomes impossible to generalize the outcome of metal debris exposure to the individual patient.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…The air pouch model consistently responds with increased cellularity in response to Co-Cr debris, although the response is not elevated over reactions to conventional UHMWPE. Direct effects of metal ions on cellular functions have been reported and include an upregulation of metallothionein I/II and increased catalase and glutathione peroxidase activity in the liver [2,40], elevated apoptosis in the local tissue [68], and chromosomal aberrations (particularly increases in the percentage of aneuploidy gain) in patients with an MoM bearing [17].…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The particles resulting from wear Volume 32, Number 2, p. 144-152, 2016 of the prosthesis are harmful to the body and induce inflammation process (Grill, 2003;Hinüber et al, 2010). Many studies have shown that Co -, Cr -, and Mo -ions are considered toxic, carcinogenic and also able to promote inflammation (Andrews et al, 2011;Hinüber et al, 2010;Jakobsen et al, 2007). Aluminum is also considered to be a risk factor for the pathogenesis of Alzheimer's disease (McLachlan et al, 1990;Rusina et al, 2011).…”
Section: Introductionmentioning
confidence: 99%